International Financial Reporting Standards (Ifrs) Convergence Effect To Accounting Conservatism - Rosy Armaini; Yevi Dwitayanti; Nurhasanah Nurhasanah (Saburai International Journal of Social Sciences and Development, 2017)
IFRS Convergence (International Financial Reporting Standards) is to adapt domestic standards to conform to IFRS (International Financial Reporting Standards). Implementation of accounting standards closely related to the selection of accounting methods. Each accounting method has a different level of conservatism. Conservatism is an attempt to choose acceptable public accounting methods that slow down the recognition of revenues, accelerate the recognition of expenses, lower the valuation of assets, and elevate the assessment of debt. This research is important to be done in an attempt to prove empirically an increase in accounting conservatism in the period after the convergence of International Financial Reporting Standards (IFRS), when compared to the period before the convergence of International Financial Reporting Standards (IFRS). The sample used in this research is PT. Indofood SuksesMakmur, Tbk with the observation period of 2010-2014. Paired-samples T-Test analysis will be used with SPSS (Statistical Package for Social Science) program Version20.Study results shows that with the implementation of a financial accounting standards (IFRS Convergence) indicating a significant differences to Accounting conservatism value in PT. Indofood SuksesMakmurTbk.